Strategi Peningkatan Kinerja UMKM melalui “UMKM Naik Kelas” Pada UMKM di Kecamatan Cempaka Putih Jakarta Pusa - Sutandi Sutandi; Resista Vikaliana; Yusup Rachmat Hidayat; Yuli Evitha (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
n Indonesia, SMEs have a strategic role and a very large contribution to the national economy by contributing 53.3% of total GDP (Gross Domestic Product). The number of SMEs in Indonesia reaches around 56.2 million units and is capable of absorbing 97.2% of the total workforce. Based on data from the Central Statistics Agency (BPS) the growth of online-based trading business has increased in the last 10 years, to 26 million or up 17% and followed by the number of SMEs reaching more than 55 million units, but many challenges must be faced by SMEs in facing MEA. The form of community service activity training is titled: "UMKM Grades Up with the subtitles Training on Inventory Management, Marketing Go Online, and Preparation of Simple Financial Statements and MSME Tax Socialization". This year 2019 is the second year of the implementation of this community service program. This year, the response of community service partners, in this case 10 Assisted Culinary MSMEs around the campus, Cempaka Putih Jakarta, were very enthusiastic. This can be seen from the spirit of curiosity (many questions) about the material of socialization and the seriousness of the training that was given. The UMKM Actors asked for the continuation of this training, in the form of assistance / consultation for the development of the UMKM. The driving factors of the UMKM Graduation Class activities are the enthusiasm or high motivation of the SMEs. While the obstacle to the implementation of this program is the lack of duration of training, in terms of frequency. Another difficulty is the limited time of the UMKM Actors, because they have to take care of the UMKM business processes that are still running. Based on the results and outcomes achieved in 2019 community service titled MSMEs Graduating Classes, then for 2020 it is planned to hold: mentoring MSME business processes, so that MSMEs truly advance in class. The intended grade is that there is progress in management, so that it has implications for increasing MSME income. To facilitate the assistance for MSME business development, a MSME staging or clustering will be conducted in Cempaka Putih District.